The influence of labor, level of education and government spending on economic growth In the city of Makassar - Aisha Usman Usman (Indonesia Accounting Research Journal, 2022)
This study aims to determine and analyze how much influence the number of workers, level of education and government spending have on economic growth in Makassar City. The hypothesis put forward is that the number of workers, level of education and government spending have a positive and significant effect on economic growth in Makassar City. The type of data used in this research is secondary data. The data is then processed using a computer program namely SPSS 16 with multiple linear regression analysis method. The results showed that the number of workers, level of education and government spending had a positive effect on economic growth in Makassar City, the regression results between the dependent variable and the independent variable were R-Square = 0.979 and F statistic = 93,